Hip joint space width in an asymptomatic population: Computed tomography analysis according to femoroacetabular impingement morphologies - Alexandre Nehme; Gerard El-Hajj; Joseph Maalouly; Rami Ayoubi; Hicham Abdel-Nour; Ramzi Moucharafieh; Raja Ashou (Elsevier, 2021)
Background: Although the association between femoroacetabular impingement (FAI) syndrome and hip osteoarthritis (OA) is well established, not all hips exhibiting cam or pincer morphologies (i.e. imaging findings of FAI syndrome) are symptomatic or arthritic. It is difficult to detect which subgroup will wear out, or how does the arthritic process start radiographically. Therefore, we measured in a retrospective study based on computed tomography (CT) analysis, the joint space width (JSW) according to a standard protocol and we investigated its variation according to the presence of a cam and/or pincer morphology. We hypothesized that the radiological presence of a cam and/or pincer hip morphologies, even in asymptomatic subjects, would affect JSW. Methods: Two hundred pelvic CT scans performed for non-orthopedic etiologies in asymptomatic patients were analyzed using a 3D software. After excluding patients with hip OA or previous hip surgery, 194 pelvic CT scans (388 hips) were retained. We measured for each hip the presence of FAI syndrome imaging findings (cam and pincer morphologies) using the classical parameters of coxometry. In addition, we performed a measurement of articular joint space width according to a standard protocol. We then calculated the mean thickness of 3 defined regions along the femoroacetabular joint: anterior-superior, posterior-inferior, and posterior-superior. Lastly, we compared the JSW across 4 groups: hips with (1) no cam or pincer, (2) pincer, (3) cam, and (4) cam and pincer morphologies using a multivariate analysis. Additionally, a topographic heatmap of JSW was plotted allowing quantitative representation of JSW along the joint. Results: Increased JSW with peak difference of 0.9 mm (25.7%) was found in hips with cam and pincer morphologies when compared to normal ones (p = 0.002) and to hips with pincer or cam morphologies only. Conclusion: Positive variations in JSW were associated to the presence of cam and pincer morphologies. This significant increase in JSW could be one of the earliest measurable changes preceding later classical alterations.